The gut microbiome and metabolites are altered and interrelated in patients with functional constipation - Li, Yan-qiu; Yan, Xiang-yun; Xiao, Xian-jun; Ma, Pei-tao; Wang, Si-qi; Liu, Hui-lin; Zhang, Wei; Chen, Min; Yao, Jun-peng; Li, Ying (Frontiers in Microbiology, 2023)
The gut microbiota and metabolites have been identified to contribute to the pathogenesis of functional constipation (FC), however, the underlying mechanism(s) have not been elucidated, and the relationship between the gut microbiota and metabolites in FC received limited attention in the literature. Herein, 16S rDNA sequencing and non-targeted metabolomic detection based on liquid chromatographymass spectrometry (LC-MS/MS) technologies were combined to analyze the altered gut microbiome and metabolic profile of fecal samples from FC patients and healthy individuals (healthy control; HC). The results indicated that the richness and diversity of gut microbiota significantly (p < 0.01) increased in FC patients. Compared with the HC group, 18 genera, including Intestinibacter, Klebsiella, and Akkermansia, exhibited statistically significant changes (p < 0.05). Metabolic analysis showed that metabolic profiles were also markedly altered with 79 metabolites, such as (-)-Caryophyllene oxide, Chenodeoxycholic acid, and Biliverdin, indicating significant inter-group differences (p < 0.05). Besides, the primary bile acid biosynthesis, as well as the metabolic profile of porphyrin and chlorophyll, were the most dominant enriched pathways (FDR < 0.01), in which Chenodeoxycholic acid and Biliverdin were significantly enriched, respectively. Correlation analysis demonstrated a strong relationship between 10 genera and 19 metabolites (r > 0.6, FDR < 0.05) and notably, Intestinibacter showed a negative correlation with Biliverdin (FDR < 0.001), which highlighted the interplay of the gut microbiota and metabolites in the pathogenesis of FC. In summary, our research describes the characteristic of the gut microbiota and metabolic profiles and the correlation between the gut microbiota and metabolites in FC patients, which may contribute to the understanding of the underlying mechanisms involved in FC pathogenesis and may provide novel insights to therapeutic interventions.